1992
DOI: 10.1002/pen.760321311
|View full text |Cite
|
Sign up to set email alerts
|

Fractography of injection molded polycarbonate acrylonitrile‐butadiene‐styrene terpolymer blends

Abstract: Fractography has been used in the post-failure analysis of single edge notched specimens of injection molded blends of polycarbonate (PC) and acrylonitrilebutadiene-styrene terpolymer (ABS). The mode of ductile tensile fracture of single edge notched specimens depended on composition. Plane stress shear tearing was observed in the composition range PC/ABS 90, ' 10 to 70/30 by weight where PC was the continuous phase. Intermediate compositions, PC/ABS 60/40 to 40/60, had a co-continuous or almost co-continuous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…The latter was mainly determined by the rubber content, and the maximum toughness was observed at around 15% rubber in the ABS. Similar highly non-monotonous variations of the fracture properties with composition are reported by other researchers (e.g., Lee et al 1992;Balakrishnan and Neelakantan 1998;Inberg 2001). In accordance with the above mentioned behavior of PC/ ABS under unnotched conditions, an enhanced fracture toughness compared to that of neat PC is only observed for sufficiently sharp notches.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…The latter was mainly determined by the rubber content, and the maximum toughness was observed at around 15% rubber in the ABS. Similar highly non-monotonous variations of the fracture properties with composition are reported by other researchers (e.g., Lee et al 1992;Balakrishnan and Neelakantan 1998;Inberg 2001). In accordance with the above mentioned behavior of PC/ ABS under unnotched conditions, an enhanced fracture toughness compared to that of neat PC is only observed for sufficiently sharp notches.…”
Section: Introductionsupporting
confidence: 67%
“…In contrast, the presence of ABS which is able to undergo volumetric expansion upon cavitation of the rubber particles causes a relief of hydrostatic stress (thereby suppressing crazing) and enables shear yielding in the PC. The qualitative picture of this toughening mechanism in PC/ABS, which is confirmed by microplastic deformations visible on the fracture surface, is generally agreed upon (e.g., Ishikawa and Chiba 1990;Lee et al 1992;Seidler and Grellmann 1993;Greco et al 1994;Ishikawa 1995;Inberg 2001). However, the efficiency of toughening strongly depends on various parameters, the rubber content in the ABS probably being the most important one.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…On the other hand, Lee et al [11] studied extensively the morphology of PC/ABS blend throughout the entire composition range. The PC-rich blends showed that dispersed ABS obtained a bead-and-string structure.…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper, their effect on polymer blends, made of polycarbonate (of bisphenol A, PC) and PMMA (plus NR-M) or PS (plus NR-SM), is discussed. These blends are related to commercial PC/ ABS blends [7][8][9][10] . Two morphologies are conceivable: the latex particles are either dispersed in one of the homopolymer phases, or they are concentrated between the phases 11) .…”
Section: Introductionmentioning
confidence: 99%